Analisis Penggunaan Aplikasi Kasir ‘’Qasir’’ Dalam Sistem Informasi Penerimaan Kas di Kala Kopi - Kartika Budiharto; Sari Andayani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze the use of the cashier application ''QASIR'' in the cash receipts information system at Kala Kopi. The object of this research is the use of cashier applications in cash receipts at Kala Kopi. The subjects in this study were employees, owners of Kala Kopi and consumers of Kala Kopi. This research is quantitative descriptive. This study uses primary data used in this study, namely the source comes from the finance department through observations, interviews and documentation conducted to employees or owners of Kala Kopi and Kala Kopi consumers who pay by cash or digital wallets (e-wallet). The secondary data used in this study are documents or records in cash receipts and presentations when using the cashier application at Kala Kopi. The results of this study were the cash receipt system at Kala Kopi was run with the help of the Qasir cashier application system. the results of the research that has been carried out, in recording cash receipts, cash and non-cash payments (e-wallet) are equally efficient as long as they are still using the